Activities of Students in Leisure-Time - Amina Smajović (Društvene i Humanističke Studije, 2023)
With the development of industry and technology, leisure time gains sociocultural importance. Leisure activities are an important predictor of personal growth and improvement of the quality of life. The purpose of this research is to examine patterns, but also to reveal tendencies and perspectives of youth spending their leisure time. 120 first and second-cycle students of the University of Sarajevo participated in the research. The results of the research showed that students put their free time into the function of rest, leisure, and personality development. They prefer to spend their leisure time with close friends or on their own. The respondents, when they do not have family, professional, and other obligations, spend their time socializing and going out, relaxing activities, and on social networks. Also, they believe that free time is essential for self-development and productivity, as well as that the biggest challenges concern the methodical organizational and methodical performance creation of free time. Accordingly, guidelines for structuring the environment are offered, which have the potential to remove obstacles and maximize educational effects in leisure time.